Characterization of causal agent of brown spot and use of silicon and manganese for disease management in rice - Mahmad Toher, Ainu Shahirah (2016)
Brown spot is one of the diseases that became a new threat to rice production and was reported to reduce the yield up to 45% under severe infection. However, pathological related information on this disease is lacking in Malaysia. This study focused on identification of the causal agent through morphological and molecular methods, as well as determination of the effects of silicon (Si) and manganese (Mn) on disease severity and PR-proteins gene expression. A total of 15 isolates were isolated, identified and screened with pathogenicity test before characterized culturally. Two isolates of Bipolaris oryae and 13 isolates of Exserohilum rostratum were identified based on morphology and internal transcribe spacer (ITS) region of rDNA. AS.P2 (Gene bank accession number KT831962) as one of the most virulent isolates in pathogenicity test was further studied for cultural characterization. Highest spore production was recorded in T2 (12 h flourescent light + 12 h complete darkness) and T4 (24 h darkness) cultured on corn meal agar (CMA) with no significant difference between them (21.67 x 106 spores/mL and 21.50 x 106 spores/mL, respectively). The lowest spore production was shown by cultures grown on malt extract agar (MEA) (0.83 x 106 spores/mL). Two sources of Si, namely calcium silicate (CaSiO3) and black rice husk ash (BRHA) were tested in combination with Mn to determine a cheaper source with the same effectiveness. Results showed significantly higher value of brown spot index (BSI) for T1 (control) where no Si and Mn were applied with 41.14%. Addition of Si and Mn increased 38.65 to 51.25% for grain yield production, if compared to T1 (control). BRHA showed good performance comparable to CaSiO3 in tiller number, percentage of filled grains, spikelet number per panicle, panicle length and 1000 grains weight. Plants treated with Mn showed differential expression of β-1,3-glucanase and chitinase with β-1,3-glucanase showed the highest expression at 2 DAI and chitinase at 1 DAI. Similarly, plants treated with Si showed differential expression of β-1,3-glucanase and chitinase with the highest expression recorded at 3 DAI and 1 DAI, respectively. This study found E. rostratum a new causal agent for rice brown spot disease in Malaysia and BRHA has the potential to be a cheaper source of Si to be applied in agriculture sector compared to CaSiO3.